Rendimiento de la canal de pollos Broilers de la línea Cobb 500 con diferentes sistemas de manejo en la época de invierno en Ecuador - Cedeño Jerez, Lelis Stalyn (2019)
IX. Summary The experimental work was carried out in the poultry facilities of the San Pablo experimental farm on the premises of the Faculty of Agricultural Sciences whose location is in the Babahoyo canton at kilometer 71/2 of the Babahoyo-Montalvo road in the Province of Los Ríos, Ecuador. The geographic coordinates are of 01º 47 "49" of South latitude and 79º 32 "of West longitude, to 8 msnm. This is an area with a humid tropical climate, an average annual temperature of 25.3ºC. Annual rainfall 1635 mm, and relative humidity of 76%. The general objective was to evaluate the performance of the Cobb 500 broiler line with different management systems during the winter season in Ecuador. It was implemented during the raising of the birds the use of balanced feed in two types of presentations, one in flour and the other the pellets, were used 3 population densities which were 10, 11 and 12 birds / m2. The trial lasted 42 consecutive days in which the 3 caps, start, growth and fattening were implemented. The results show that the feeding with pellets had a better response compared to the feeding in flour. The effect of the variants of the food only shows in the variables live weight of the carcass of the breast and in the densities only for the weight of the head . It also informs us that the density 12 birds / m² has results in the variables studied that support its use. It was demonstrated that they can be used in the Ecuadorian tropics giving very good results giving a production of more live weight per m2. Keywords: Line, Cobb 500, handling, channel, densities, chickens, broilers.